Presidential Address, 1970 Men for Minerals (The Australasian Institute of Mining and Metallurgy, 1970)
This evening I would like to speak about men for the mineral industry.It is trite to say that the mining industry is expanding rapidly and that technically trained men are in short supply. How short is difficult to assess and impossible to quantify.The industry has been traditionally managed by technically trained men experienced in the ways of their fellow men. Let us start with the assumption that men with this training and experience are essential to management of mining and metallurgical enterprises.I suggest that we do this as it avoids argument with those who are beginning to suggest that such men are not so important as they used to be; who are suggesting that the latest sophisticated business management schools can produce managers who can straight out of school join the upper echelons of an organization and successfully manage it by the use of modern systems and techniques without the need to rub shoulders with men of all callings and get their hands dirty in the process.This kind of thinking brings to mind the modern cargo ship which is equipped with all the latest gadgets of science. It can find its way from Sydney to Auckland with no one in the engine room and the man on the bridge spending most of his time writing to his wife or reading the latest novel.How often do we read of this ship being tied up in Sydney because the crew sympathizes with the cook who has been slighted by some uncomplimentary remark about his toheroa soup? Here is a pieceof sophisticated machinery stopped through no technical fault, but held up by the whim of man. The understanding of man by man can spell the success or failure of any endeavour. A single man can leadan organization to the pinnacles of success, or doom it to utter failure in spite of modern systems and techniques.So let us start from the point that people matter.Through the years our Institute has been fortunate in having many members who have felt strongly...